Multi-modes control for three-phase bidirectional AC/DC converter for hybrid AC/DC microgrids - Wang, Jun Jun (2015)
Hybrid AC/DC microgrids are developed to improve the efficiency reduce due to multiple reverse conversions between individual AC and DC grids. Three-phase AC/DC bidirectional converters are used to interlink AC and DC microgrids and connect to the utility grid. The bidirectional converter should operate in stand-alone inverter mode, grid-connected inverter or rectifier modes base on the DC and AC source connection. This report designs a control system for the three-phase AC/DC bidirectional converter that can achieve seamless transition between different modes. Dq0 transform is used to transform abc domain into dq domain. The seamless transition is achieved by a generic current inner loop. Outer loop performing the corresponding regulations are designed for each operation modes. PLL is used to track the phase angle and amplitude of AC voltage. The control system is verified with both simulation and experimental results.